POLITICAL ASPECTS OF HYDRO-ENERGY PROBLEMS IN CENTRAL ASIA - H. H. Hurramov (Проблемы постсоветского пространства)
In article political aspects of hydro-energy crisis in Central Asia are analyzed. The main reasons for disagreements of the countries of the region on the matter are investigated. Positions of the Central Asian countries are revealed.